Effectiveness of Gargling with Lemon Juice (Citrus lemon) and Betel Leaf Decoction on Debris Index and Saliva pH of Elementary School Students in Aceh Besar District - Rahayu, Eka Sri; Salfiyadi, Teuku; Reca, Reca (Journal of Health Science and Medical Therapy, 2024)
This study aims to evaluate the effectiveness of gargling with lemon juice (Citrus lemon) and betel leaf decoction (Piper betle) on the Debris Index and saliva pH among elementary school students in Aceh Besar District. The background of this research is rooted in the high prevalence of dental caries and other oral health issues in Indonesia, particularly among children. The methodology employed is a quasi-experimental design with two treatment groups, where one group gargles with lemon juice and the other with betel leaf decoction. The results of the study indicate that gargling with betel leaf decoction significantly increases saliva pH (an increase of 1.34) and reduces oral acidity, which is crucial for preventing enamel demineralization and lowering the risk of cavities. Conversely, lemon juice demonstrates a significant reduction in the Debris Index (a decrease of 1.3), highlighting its effectiveness in cleaning plaque and food residues from teeth in the short term. While lemon juice is effective for quick cleaning, its use must be approached with caution due to its strong acidic nature, which can damage tooth enamel if used excessively. In conclusion, this study asserts that betel leaf decoction is superior for long-term use in maintaining oral health, while lemon juice is more effective for quick cleaning but should be used judiciously. These findings emphasize the importance of selecting appropriate oral care methods, particularly in populations at higher risk for dental issues.